The Study of A Improve Model For The D-D Nuclear Fusion Reaction Cross Section - Majeed, Raad H.; Mohammed, Laheeb A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study of improved model for measuring the total nuclear fusion cross section characteristics the D-D reaction may play an important role in deciding or determining the hot plasma parameters such as mean free path , the reaction rate , reactivity and energy for emitted neutrons or protons in our work we see the it is necessary to modify the empirical formulas included the total cross section in order to arrive or achieve good agreement with the international publish result.